INOVASI PRODUK HALAL BERBASIS TEKNOLOGI SEBAGAI STRATEGI KEUNGGULAN KOMPETITIF UMKM HALAL : KAJIAN LITERATUR - Fauzi, Mustofa Mahfudz (Taksasila Edukasi Insani, 2025)
Halal MSMEs play a strategic role in the development of the national economy, especially in meeting the needs of the growing halal product market. This study aims to examine how technology-based product innovation can be a primary strategy in increasing the competitive advantage of halal MSMEs. Through a qualitative approach with a literature review, it was found that the use of technologies such as blockchain, digitalization of halal certification, digital marketing, and the use of IoT can improve operational efficiency, supply chain transparency, and expand market reach. However, challenges such as low digital literacy, high technology implementation costs, and infrastructure limitations are still significant obstacles. Great opportunities are open thanks to the growth of the global halal market, government policy support, and the digitalization trend among Muslim consumers. This study emphasizes the importance of strengthening human resource capacity, cross-sector collaboration, and the implementation of adaptive technology-based strategies to strengthen the competitiveness of halal MSMEs in a sustainable manner.Keywords: Halal innovation, MSMEs, digital technology, competitive advantage, digitalization